O traço e a trama dos anos 50 por Carlos Estevão - Person, Eliane (2011)
Having as a starting point the trace as text, this dissertation presents, as its main objective, to bring about the social plot of the 1950s in the city of Rio de Janeiro as the federal capital, in the light of the humoristic representation of Carlos Estevão in O Cruzeiro. Through the imagetic humor of one of the most popular and representative artists of the biggest magazine in terms of circulation in that decade, the aim was to visualize experiences and ruptures in the established system, located in the structure generated inside a society which lay in an apparent territory of calmness and in a dream of modernity , projecting a hegemonic speech, which at the same time, alienated the multiple life experiences of the several social subjects inserted in the complexes of their daily lives. Conceiving culture as a polyphonic instance, in the view of Bakhtin s theoretical and methodological statements, this research sought to favor the emergence of the plural voices present in the artist s flow of imagetic plots, which appeared in Estevão s various humor series, as it contemplated and intertextuality of sources. Facing this problem, the focus was to give priority to the analysis of the imagetic production located into the city s routine, seeking to capture the various groups dynamics, resulting in the emergence of the silenced and invisible individuals, also exposing the existence of conflicts and social tensions, which underlie the social plots in the context of transformation into a cosmopolitan and urban society. Following these aspects, the problematization of the series related to the emergence of a middle class consumption society seeking to socially ascend, which would allow people a criticism towards the modernization speech and would reveal the deep distance between real life and the ideal country projected as a target. In this view, opposing Carlos Estevão de Sousa s imagetic humoristic narrative to that modernity speech, represented the confrontation related to the built memory of the period as well as the delimitation of his trace and plot critical potentiality. The broadness of the sources analyses present in o Diário da Noite and in O Jornal favored the establishment of the humor representation about the country, the nation and the people as well, completing a picture of problematizations about the historically established memory in the period, in the same manner as it enabled the visibility of the resistance and compliance of the various individuals and social groups